Histomorphological studies on prenatal development of reticulum in buffalo (Bubalus bubalis) - SINGH, OPINDER; ROY, K S; BAWA, B S; MALHOTRA, VANEET (The Indian Journal of Animal Sciences, 2014)
Histomorphological studies were made on the reticulum of buffal 0 foetii with crown rump length ranging from 5.0 cm to 62.0 cm. The lamina epithelialis was divisible into dark basal and light superficial zones. The cells varied from cuboidal to columnar in basal zone and were polyhedral in superficial zone. The papillae of lamina propria were initially observed at 14.7 cm CRL. The mucosal surface showed compartments characteristic of reticulum at 19.6 em CRL. The typical honeycomb appearance was observed at 38 cm CRL. The reticular papillae exhibited muscle bundles in apical portion at 60.1 cm CRL and were comparable to adult. The tunica muscularis was comprised of inner circular and outer longitudinal smooth muscle cells although reverse orientation of muscle fibres was also observed.